0318 Prospective Association of Actigraphy-Assessed Sleep with Physical Growth in the First 6 Months of Life. (27th May 2020) - Li, X; Rueschman, M; Kaplan, E R; Yu, X; Davison, K; Redline, S; Taveras, E M
Abstract: Introduction: Suboptimal sleep is associated with weight gain and related chronic diseases in adults, adolescents, and older children. However, little is known regarding the associations between sleep and physical growth in infants. We investigated prospectively the associations between objectively-measured sleep patterns at 1 month and physical growth in the first 6 months of life. Methods: We studied 344 full term infants in the ongoing longitudinal Rise & SHINE (Sleep Health in Infancy & Early Childhood) birth cohort study. At 1 month, infants underwent 7-day ankle actigraphy, estimating average sleep duration (24-hour, nighttime, and daytime) and sleep fragmentation (number of nighttime awakenings). Weight and length were measured at birth and 6 months and used to calculate weight-for-length z (WFL-z) scores. We used linear and logistic regression analyses to examine the associations between sleep patterns at 1 month with WLF-z at 6 months and rapid weight gain from birth to 6 months, defined as an increase in WFL-z greater than or equal to 0.67, controlling for covariates. Results: Each 1-hour increase in 24-hour sleep duration was associated with a 0.07-unit (95% CI [0.01, 0.12]) increase in WFL-z at 6 months. Daytime, but not nighttime, sleep duration was positively associated with WFL-z. Greater number of nighttime awakenings was associated with higher WFL-z (beta = 0.28; 95% CI [0.08, 0.49]). 24-hour and nighttime sleep duration were positively associated with a 18.5% (95% CI [1.04, 1.35]) and a 23.4% (95% CI [1.02, 1.49]) higher odds of rapid weight gain from birth to 6 months, respectively. Conclusion: Longer 24-hour sleep duration was associated with higher 6-month WFL-z and more rapid increases in WFL-z from birth to 6 months. Greater nighttime sleep fragmentation was associated with higher 6-month WFL-z. Sleep at 1 month might provide modifiable targets to help avoid lifetime complications of excess weight. Support: R01DK107972.